Hubungan antara Self Regulated Learning dan Kelekatan Remaja Awal terhadap Ibu dengan Prestasi Belajar Siswa SMP N 6 Denpasar - Putri, Putu Riana Artyanti; Rustika, I Made (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
One of the main aims the achievement of adolescents is the achievement of learning. The teens looked at the successes and failures in achieving the feat would be a prediction for the success and failure when adult. Accomplishment of learning is influenced by many factors that originate from internal factors or external factors of students. One of the internal factors that may affect the achievement of student learning is the ability of the students in applying self regulated learning and from external factors, adolescents against parental attachment to mother can be one of the factors that affect the achievement of student learning. The purpose of this research is to know the relationship of the self regulated learning and adolescents attachment against the mother with the learning achievements of the adolescents in school. The subject in this study is students of class VIII SMP N 6 Denpasar chosen with stratified random sampling as many as 150 students. Instrument in this study is self regulated learning scales, attachment scale and scale data student report cards. Student report cards data on the research data is unnormal distribution, then the analysis of the data used in this research is the analysis of correlation Spearman's. From the results of the analysis of correlation Spearman's correlation coefficient shows the value of self-regulated learning with the learning achievements of 0,320 (p=0.000) and the correlation coefficient adolescents attachment against the mother with the learning achievements of 0,196 (p=0,016). From the results of the analysis performed looks that the correlation coefficients of Self-regulated learning with greater achievements as compared with correlation coefficient of adolescents attachment against the mother.Keywords: Achievements, self regulated learning, early adolescents attachment with mother , early adolescents